Outcome and Incidence of Re‐Intervention After Surgical Repair of Tetralogy of Fallot1. Issue 1 (28th November 2012) - Bakhtiary, Farhad; Dähnert, Ingo; Leontyev, Sergey; Schröter, Thomas; Hambsch, Jörg; Mohr, Friedrich Wilhelm; Kostelka, Martin
Abstract Objectives: Timing of primary repair of tetralogy of Fallot (TOF) remains controversial. We evaluated the long‐term outcome of early primary treatment strategy in a patient cohort with TOF less than eight months of age. Methods: A group of 120 patients with TOF less than eight months of age (5 ± 2.4 months) underwent early primary repair of TOF between October 1998 and August 2009. Sixty‐one patients received a transanular (TAN) repair, and 59 patients received a right ventricular outflow tract (RVOT) + main pulmonary artery (MPA) double patch repair with concomitant pulmonary valve reconstruction. Result: There was no early or late mortality. The follow‐up was 100% completed. There were eight reoperations and eight patients underwent catheter intervention for severe pulmonary valve insufficiency or stenosis, obstruction of right ventricular outflow tract, and stenosis of pulmonary arteries. Actuarial survival was 100% at ten years. At latest follow‐up 80 patients were in NYHA Class I without any antiarrhythmic medications. On latest echocardiography, 90 (75%) patients had mild to moderate pulmonary regurgitation, and 10 had a right ventricular outflow tract gradient more than 40 mmHg. Conclusions: These data strongly support the concept of early primary repair of TOF in patients with well developed pulmonary arteries. Early primary repair is associated with an excellent early and late outcomes, an acceptable risk of reoperation and re‐intervention, and a low incidence of significant right ventricular dysfunction.